Historical and cultural similarities to sister city collaboration efforts between Tanjungpinang (Indonesia) and Johor Bahru (Malaysia) - Swastiwi, Anastasia Wiwik; Rani, Marnia; Putri , Rizqi Apriani; Pratiwy, Devi; Zulha, Mimi Audia; Fadilla, Titik Nur (Faculty of Social and Political Science, Universitas Airlangga, 2024)
Sister city cooperation based on common historical and cultural ties between Tanjungpinang, Indonesia and Johor Bahru, Malaysia provides a strategic opportunity to enhance socio-cultural interaction and encourage tourism. This research aims to find opportunities for sister city collaboration and the types of activities that are included in the scope of cooperation between the two cities. The method used in this research is descriptive with a qualitative approach by collecting various data, including official government documents, local demographic statistics, socio cultural characteristics, economic situation, development plans, and public and government views regarding social and development activities. To analyze the phenomena that occur, the theory of liberalism is used which states that a country can achieve political and economic goals through cooperation and promoting individual freedom and social justice. The results of this study indicate that the collaboration can be an effective platform for the exchange of knowledge, practices and resources between the two cities, and can also expand the network of partners involved in inclusive education. The study concluded that there are still several challenges such as limited resources, lack of public awareness and understanding, and structural barriers that can affect the effectiveness of implementing this collaborative effort. Thus, an active and collaborative role is needed from state and non-state actors to achieve sustainable economic and tourism goals.